MEREFLEKSIKAN HUBUNGAN ANTARA ETIKA ARISTOTELIAN DAN BISNIS DENGAN STUDI KASUS LUMPUR LAPINDO - Agustinus W. Dewantara (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2013)
Oftentimes, the link between ethics and business escapes our notice. Business practices in Indonesia often wax corruptive and conspiring, with the misuse of representation and power, and rife with immorality. Yet, business is precisely often related to economic power and the ways of controlling it. Ethics allows the science of business to develop virtues through each action that involves the use of economic power. Truly ethical conduct is the dream of every man. That is why doing business should not be equated to